The Demand for Subsidized Housing: A Case of Banda Aceh City, Indonesia - Nazamuddin, B.S.; Masri, Fadhillah; Fitriyani, F. (Universitas Syiah Kuala, 2022)
Objective The Indonesian government has introduced the Housing Financing Facility (FLPP) scheme. The subsidized housing scheme is intended to help low-income families improve their welfare. Understanding how mortgage subsidies affect the demand for new houses can provide a better understanding of how housing policy affects the number of people who afford to own homes, house prices, and other social welfare outcomes. This study investigated the effects of income, housing value, education and family size on the demand for subsidized housing in Banda Aceh.Design/methodology The methodology used in this paper is multiple regression method which was collected from household data of 60 respondents from six sub-districts in Banda Aceh City, Indonesia.Results The study found that only income and housing values were statistically significant in determining the demand for subsidized housing. Meanwhile, the purchase of subsidized housing does not depend on the size and education of the family. These findings suggest that households tend to buy larger size homes as incomes rise and seek to maximize their benefits from buying subsidized homes even at higher prices, which is proxied by the value of the home, since housing is considered a housing investment.Research limitations/implications The policy implications of these findings are that governments should make predictions of future needs for subsidized housing based on income growth. The government should also accelerate affordable housing funding schemes, as the long-term economic growth impact of such policies is positive.